Video Project Model for Increasing English Speaking Skills in Covid-19 Pandemic - Rifari Baron (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of the study was to know the increase of English speaking using video project.  Moreover, the covid-19 pandemic era needs a learning process that can give appropriate facility for online learning. The method of study used one-group experimental. The participant was 25 students that are taken randomly. Data analysis used paired sample t-test. The results showed that there was an increase in the ability to speak English. From each component of the ability to speak English, the average score also increased. This has implications for understanding the concept of using facilities or appropriate learning methods. The concept of learning and teaching management must be by the backgrounds and needs of students.